INTENSIFIKASI ADMINISTRATIF DALAM PENGEMBANGAN PROFESIONALISME GURU: DINAMIKA KEBIJAKAN DI INDONESIA DENGAN RUJUKAN SINGAPURA - Hasanah, Siti Nur; Mashudi; Ubaidillah; Nawangsari, Dyah (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2026)
This study examines how teacher professional development policies shape administrative intensification, with a particular focus on Islamic Religious Education (PAI) teachers in Indonesia, using Singapore as a comparative policy reference. It aims to analyze how policy architecture configures administrative workload and professional learning. This study employs a qualitative approach using document analysis combined with comparative policy analysis. Data were collected from official national policy documents, including regulations on teacher workload, professional allowances, performance appraisal systems, and career development frameworks. Data analysis was conducted through systematic coding and thematic analysis based on administrative burden theory and policy enactment perspectives. The validity of the analysis was ensured through iterative reading, coding consistency, and triangulation with relevant empirical literature. The findings reveal that in Indonesia, credit-based professional development requirements, layered verification mechanisms, and decentralized governance generate cumulative administrative obligations that extend beyond instructional improvement. For PAI teachers, this condition creates tensions between administrative compliance and value-based pedagogical practices that are not easily captured through standardized documentation. In contrast, Singapore’s integrated governance model embeds professional growth within a coherent system that aligns appraisal, mentoring, and career progression, thereby minimizing fragmented reporting. This study argues that administrative intensification is a structural outcome of policy design rather than merely an implementation issue. By reframing teacher workload as a governance effect, this research contributes a comparative perspective on how accountability systems can be designed to support professional competence development, particularly in value-oriented educational contexts.